2018
DOI: 10.3847/1538-4357/aaa9bc
|View full text |Cite
|
Sign up to set email alerts
|

SDSS IV MaNGA: Dependence of Global and Spatially Resolved SFR–M Relations on Galaxy Properties

Abstract: The galaxy integrated Hα star formation rate-stellar mass relation, or SFR(global)-M * (global) relation, is crucial for understanding star formation history and evolution of galaxies. However, many studies have dealt with SFR using unresolved measurements, which makes it difficult to separate out the contamination from other ionizing sources, such as active galactic nuclei and evolved stars. Using the integral field spectroscopic observations from SDSS-IV MaNGA, we spatially disentangle the contribution from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Cano-Díaz et al (2016) find no clear M dependence in the Σ − Σ SFR relation for CALIFA galaxies. Pan et al (2018) find some trends between M and the Σ − Σ Hα relation, exhibiting a similar flattening in the relation at higher M , but attribute this to the influence of ionisation mechanisms other than star formation. However, other studies (e.g.…”
Section: Dependence On Galaxy Stellar Massmentioning
confidence: 83%
“…Cano-Díaz et al (2016) find no clear M dependence in the Σ − Σ SFR relation for CALIFA galaxies. Pan et al (2018) find some trends between M and the Σ − Σ Hα relation, exhibiting a similar flattening in the relation at higher M , but attribute this to the influence of ionisation mechanisms other than star formation. However, other studies (e.g.…”
Section: Dependence On Galaxy Stellar Massmentioning
confidence: 83%
“…cloud of points well below the SFMS). The agreement between global and local relations was already explored in detail by Pan et al (2018) and Cano-Díaz et al (2019), being in general good.…”
Section: The Intensive Global Relationsmentioning
confidence: 87%
“…More recently, some studies have found that the SFMS relation has a local (spatially-resolved) counterpart in the diagram that relates the SFR surface density (Σ S FR ) with the stellar mass surface density (Σ * ) (Sánchez et al 2013;Wuyts et al 2013;Magdis et al 2016;Cano-Díaz et al 2016;Maragkoudakis et al 2017;Abdurro'uf & Akiyama 2017;Hsieh et al 2017;Pan et al 2018;Ellison et al 2018;Medling et al 2018;Erroz-Ferrer et al 2019). This spatially resolved diagram aims to look for the star formation process at a local level within the galaxies (at ∼kpc scales).…”
Section: Introductionmentioning
confidence: 99%